ANALISIS DAMPAK TEKNOLOGI DIGITAL TERHADAP PENGEMBANGAN EKONOMI LOKAL DESA - Syahrul, Syahrul (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
This research aims to analyze the impact of digital technology on local economic development in villages, with a focus on the agricultural, handicraft and local trade sectors. Although the adoption of digital technology in villages is still limited, the implementation of digital platforms such as social media and e-commerce has had a positive impact on market access and operational efficiency. Village entrepreneurs who utilize digital technology report increased market access and easier transactions. However, major challenges such as limited digital skills and uneven internet infrastructure still hinder the potential of digital technology. Village governments and educational institutions have an important role in accelerating technology adoption by providing digital literacy training and increasing internet access. These findings suggest the need for closer collaboration between government, educational institutions and communities to maximize the benefits of digital technology in local economic development in villages. Penelitian ini bertujuan untuk menganalisis dampak teknologi digital terhadap pengembangan ekonomi lokal di desa, dengan fokus pada sektor pertanian, kerajinan tangan, dan perdagangan lokal. Meskipun adopsi teknologi digital di desa masih terbatas, penerapan platform digital seperti media sosial dan e-commerce telah memberikan dampak positif terhadap akses pasar dan efisiensi operasional. Pengusaha desa yang memanfaatkan teknologi digital melaporkan peningkatan akses pasar dan transaksi yang lebih mudah. Namun, tantangan besar seperti keterbatasan keterampilan digital dan infrastruktur internet yang tidak merata masih menghambat potensi teknologi digital. Pemerintah desa dan lembaga pendidikan memiliki peran penting dalam mempercepat adopsi teknologi dengan memberikan pelatihan literasi digital dan meningkatkan akses internet. Temuan ini menyarankan perlunya kolaborasi yang lebih erat antara pemerintah, lembaga pendidikan, dan masyarakat untuk memaksimalkan manfaat teknologi digital dalam pengembangan ekonomi lokal di desa.